Multiple cavitating pulmonary nodules secondary to Hodgkin's lymphoma - Abdul Azih, Muhammad Naimuddin; Abd Rahman, Azlina; Hin, Howsoon; Chunn, Kuan Yeh (International Islamic University Malaysia, 2017)
We report a 26-year old lady who presented with chronic cough and breathlessness associated with subtle TB symptoms for 1 year. Her CT thorax showed multiple cavitating pulmonary nodules with mediastinal and cervical lymphadenopathy. Cervical lymph node biopsy and CT-guided pulmonary biopsy at our centre confirmed the diagnosis of Hodgkin’s lymphoma with pulmonary infiltrations. She was successfully treated with ABVD regime but later developed life-threatening bleomycin-induced pulmonary fibrosis. Sadly, she succumbed to respiratory failure due to severe pneumonia with possibility of bleomycin-induced pulmonary fibrosis. Multiple cavitating pulmonary nodules secondary to lymphoma is rare and in TB endemic area, it may result in delayed diagnosis and treatment.